ANALISA TENTANG LEGALITAS PERSIDANGAN PEMBUKTIAN MENURUT PASAL 25 PERMA NOMOR 1 TAHUN 2019 TENTANG ADMINISTRASI PERKARA DAN PERSIDANGAN DI PENGADILAN SECARA ELEKTRONIK - Mutiara Seroja; Firdaus Firdaus; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The world has entered the Era of the Industrial Revolution, wherecomputerization and digitalization processes have occurred and have affectedalmost all aspects of human life, including the legal system. This causes courtinstitutions to rely on technology to support the continuity of legal services tojustice seekers. This online trial applies to both criminal and civil cases. For civiltrials, use a special application called E-Court or E-Litigation.The type of research used by researchers is normative legal research orwhat is known as